The Relationship between Transpiration Speed and The Number of Stomata of Adam Hawa Plants (Rhoeo discolor) at The Veteran Bangun Nusantara University Campus - Nur Rokhimah Hanik; Dewi Syafitri; Rahma Kusuma Ningati; Luthfiyah Zulfaa Astari; Asma Asy Syifaiyah; Suci Nurhayati (Jurnal Biologi Tropis, 2023)
The physiological and anatomical adaptation of the Rhoeo discolor plant to water conditions in the environment can be used as a learning resource/study material for plant physiology courses. One example of physiological and anatomical adaptation is the relationship between transpiration rate and number of stomata. Therefore, it is necessary to conduct research on the relationship between transpiration rate and number of stomata in Rhoeo discolor plants at the University of Veteran Bangun Nusantara campus. Measurement of the rate of transpiration used Clobat Clorite paper and counted the number of stomata by making an incision in the lower epidermis of the leaf. Data analysis on the relationship between transpiration rate and number of stomata used prodact moment and qualitative descriptive to determine differences in transpiration rate and number of stomata in Rhoeo discolor leaves. From the research results it can be concluded; There is a relationship between the speed of transpiration and the number of stomata of the Adam Hawa plant (Rhoeo discolor) on the campus of the University of Veterans Bangun Nusantara, but the relationship is very small (r = 0.298). Discolor rhoeo plants that are in dry, dry shaded, and humid environments have different transpiration rates and number of stomata. Anatomically and physiologically the Rhoeo discolor plant can be used as a source of learning and an ornamental plant so that this plant needs to be cultivated and planted in more locations within the Veteran Bangun Nusantara University campus.